pi-Extended cis-configured unsynimetrical squaraine dyes for dye-sensitized solar cells: panchromatic response - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2019)
{Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light harvesting efficiency is limited with the narrow absorption 20 profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye-dye interaction that leads to broadening the absorption profile, the contribution of the aggregated state to the power conversion process is found out to be poor. Here, we have engineered far-red active pi-extended cis-configured unsymmetrical squaraine dyes with carboxylic acid and cycnoacetic acid as anchoring groups with controlled aggregation and panchromatic light absorption by including the steric and electronic factors. The presence of sp(3)-C (out-of-plane) and N-alkyl (in-plane) groups played an important role in modulating the assembly of the dyes on the TiO2 electrode; the cis-squaraine unit helps to extend the conjugation in the NIR region besides enhancing the visible transition and the incident photon-to-current conversion efficiency profile that showed the importance of anchoring groups for the panchromatic response. Dye PSQ10 showed solar-to electric conversion with an onset of 850 nm with the device performance of 7.0% (V-oc = 0.581 V, J(sc) = 17.06 mA/cm(2)
Keywords: cis-squaraine dyes; Dye aggregation; Dye-sensitized solar cells; extended far-red absorption; panchromatic response